Synergistic Development Pathways: An Exploratory Study on the Urban–Rural Mutual Assistance Model and Low-Carbon Transformation of Henan’s Power Supply Industry Towards Dual-Carbon Goals - Xinfa Tang; Guozu Hao; Yonghua Wang; Youwei Wan; Jingjing Wang; Yan Luo; Musa Dirane Nubea (Energies)
In the midst of the push for dual-carbon goals, urban centers are faced with the imperative of reducing emissions and conserving energy, while rural regions are harnessing their abundant new energy resources to promote balanced urban–rural development. Photovoltaic (PV) power generation, known for its cleanliness, safety, and emission-free nature, is playing a crucial role in the evolution of Henan Province’s power supply industry. This paper delves into the current state of Henan’s power supply infrastructure, the trajectory of its low-carbon development, and the policies that shape the PV sector. It also examines the establishment of an urban–rural mutual aid model through the lens of alternative energy technologies. By utilizing a combination of case studies and systematic theoretical research, this paper uncovers the economic potential that remains untapped of new energy sources in rural areas and presents strategies for synergistic development in alignment with dual-carbon goals within the power supply industry. The research underscores the significance of an urban–rural mutual assistance model in achieving carbon neutrality, addressing urban–rural development gaps, fostering shared prosperity, and contributing Chinese insights to global climate governance frameworks.